Reckless Ruby - Oram, Hiawyn (HarperCollins Publishers Ltd, 1993)
Ruby does any thing she can-including crossing canyons on tightropes and dangling from skyscrapers by her shoelaces--to defy her mother's expectations and forge her own identity.
Keywords: Juvenile literature-Fiction